Analisis Peran Pojok Baca terhadap Literasi Siswa di SDN 238 Palembang - Syarifah Salsabila (Universitas Pendidikan Indonesia (UPI), 2023)
This research is to analyze the Role of Reading Corner on Student Literacy at SD Negeri 238 Palembang. The subjects used were grade 2 students. This study used a qualitative descriptive method of observation and documentation. The results of this study indicate that the Reading Corner has a very important role in the development of Student Literacy. Reading is an important activity in the teaching and learning process, because reading is the ability to transfer knowledge through text or reading material. Reading corner activities are carried out as an effort to increase students' interest in reading which is applied as a habit and aims to develop a culture of literacy in schools through reading corner activities. Through the Reading Corner, students can add extensive knowledge and insight through reading in the Reading Corner. The Reading Corner is placed in the corner of each class, which contains several fairy tale books or story books, etc. Students can read in the Reading Corner during their free time.